Women in clinical trials: a review of policy development and health equity in the Canadian context - Alla Yakerson (BMC, 2019)
Abstract Health equity in pharmaceutical research is concerned with creating equal opportunities for men and women to partake in clinical trials. Equitable representation is imperative for determining the safety, effectiveness, and tolerance of drugs for all consumers. Historically, women have been excluded from participating in clinical research leading to a lack of knowledge regarding drug effects and their consequences. This paper examines the changes made since the implementation of Canadian policies on the representation of women in clinical trials, the analysis of sex and gender, as well as the discourses that are prominent among researchers. A feminist ethics framework is used to examine the structures that endeavor to elucidate women's involvement in trials, as experienced under extensive patriarchal history. Scholarly literature and Canadian government policy documents are used to explore the development of clinical trials as pertaining to sex and gender. Findings suggest that women continue to be underrepresented or excluded from important research, highlighting ongoing ethical and justice concerns. Improvement recommendations for policies are outlined.